Sustainability Innovations in the Electricity Sector - Jansen, Dorothea; Ostertag, Katrin; Walz, Rainer; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2012)
The future of modern societies depends on their ability to deal with the challenge of climate change in the coming decades. One essential component is a better understanding of innovation processes in the energy sector. This book focuses on sustainability innovations in renewable energies, combined heat and power, and energy service contracting, and analyses the institutions, actors and functions within the innovation system. Of particular interest is the question of whether the joint effect of EU-driven market liberalization and climate policies will succeed in establishing market forces that will drive actors towards more climate-friendly energy production. A special focus is on the role of local utilities in the electricity sector as opposed to large transmission net operators or regional net operators. The countries covered in the contributions include Germany, Denmark, the UK, Switzerland, and the Netherlands.
Preface -- 1 Local Utilities in the German Electricity Market and their Role in the Diffusion of Innovations in Energy Efficiency and Climate Change Mitigation -- 2 Contracting and Mikro-KWK - the Role of Municipal Utilities in Germany -- 3 Governance variety in the energy service contracting market -- 4 Cooperation and Shareholding Among Local Utilities - Driving Factors and Effects -- 5 Local Utilities Under the EU Emission Trading Scheme: Innovation Impacts on Electricity Generation Portfolios -- 6 Exploring the Linkages Between Carbon Markets and Sustainable Innovations in the Energy Sector - Lessons from the EU Emissions Trading Schemes -- 7 Microgeneration in the UK and Germany from a Technological Innovation Systems Perspective -- 8 Innovation and Diffusion of Renewables and CHP in the UK: Regulation and Liberalisation -- 9 The Context of Innovation: How Established Actors Affect the Prospects of Bio-SNG Technology in Switzerland -- 10 Identifying Typical (Dys-) functional Interaction Patterns in the Dutch Biomass Innovation System.
Keywords: Business; Energy policy; Energy and state; Management; Industrial management; Political science; Environmental economics; Sociology; Business and Management; Innovation/Technology Management; Environmental Economics; Energy Policy, Economics and Management; Sociology, general; Political Science; Electronic books